(untitled) (Impact: Journal of Transformation, 2026)
This paper is premised on the findings of a study that aimed at investigating factors influencing the performance of the Order of Saint Augustine agricultural project in Evurore ward, Embu County. The specific objectives of the study were: to evaluate the influence of participation by key institutional community stakeholders on the performance of the OSA Project in Evurore ward, and to examine the influence of farmer group participation on the performance of the OSA Project in Evurore ward. The study was motivated by the growing concerns of the failed agricultural project performance of the OSA agricultural project in Mbeere North, Embu County. The study was based on participatory theory and employed a descriptive research design. The target population consisted of 300 farmers participating in the OSA agricultural project. The study collected quantitative data through structured questionnaires. Inferential and descriptive statistical techniques were used to analyse the quantitative data using SPSS, such as mean, percentages and standard deviation and were presented in tables. The results showed evidence of a significant positive relationship of farmer group participation (P =0.000, r =0.793) and project performance. Additionally, there was positive relationship between community stakeholders (p =0.000, r =0.51) and project performance. The study recommended that policymakers should strategically emphasise farmer group participation and stakeholder participation to further improve the performance of the OSA agricultural projects in Evurore ward, Embu County